2012
DOI: 10.1159/000342517
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Nontuberculous Mycobacteria: Advantages and Limits of a Broad-Range Sequencing Approach

Abstract: The isolation of nontuberculous mycobacteria (NTM) from clinical specimens has become very common in recent years. Such organisms are typically environmental and occasionally pathogenic for humans and animals. Standard diagnosis of mycobacterial infections relies on direct examination and culture. However, molecular tools are now available which allow quicker and more accurate diagnosis. Detection of NTM can be performed directly from clinical samples, although identification is mostly carried out after isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…Gene sequencing and chromatographic analysis of lipids using HPLC and gas-liquid chromatography methods are technically cumbersome, relatively expensive, and available in only a few specialized clinical laboratories (12). DNA sequencing using 16S rRNA alone cannot differentiate between closely related rapidly growing mycobacterial species, including M. chelonae and the M. abscessus group and between M. mucogenicum and M. phocaicum, and it requires the use of hsp65 or rpoB sequencing (15 (18,22). Further studies are warranted with additional mycobacterial strains, especially those belonging to the groups and complexes so as to improve the discrimination capabilities for these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene sequencing and chromatographic analysis of lipids using HPLC and gas-liquid chromatography methods are technically cumbersome, relatively expensive, and available in only a few specialized clinical laboratories (12). DNA sequencing using 16S rRNA alone cannot differentiate between closely related rapidly growing mycobacterial species, including M. chelonae and the M. abscessus group and between M. mucogenicum and M. phocaicum, and it requires the use of hsp65 or rpoB sequencing (15 (18,22). Further studies are warranted with additional mycobacterial strains, especially those belonging to the groups and complexes so as to improve the discrimination capabilities for these species.…”
Section: Discussionmentioning
confidence: 99%
“…Other targets for molecular technique-based species identification of mycobacteria include the heat shock protein (hsp65) gene, the intergenic gene between 16S and 23S, and the gene coding for the beta subunit of RNA polymerase (rpoB) (9-11). Molecular techniques have helped greatly to improve the turnaround time; however, these require a high level of expertise and a special laboratory setup (13)(14)(15). High-pressure liquid chromatography (HPLC) for the analysis of mycolic acids (␤-hydroxy-␣-fatty acids) is also used to identify mycobacteria from culture; however, this technique is available in only a few specialized laboratories (12).…”
mentioning
confidence: 99%
“…In specialized laboratories, molecular tests are available for rapid identifications of most common NTM species. Sequencing of genomic targets (such as 16S rRNA) allows accurate and rapid identification, even if some technical limitations exist, such as in case of samples with polymicrobial patterns and the deficiencies in public sequence databases [ 53 ].…”
Section: Challenges In Ntm Diagnosis In Patients With Non-cf Broncmentioning
confidence: 99%
“…Roth et al demonstrated that in situations where 16S rRNA gene sequences were indistinguishable, such as for M. kansasii and M. gastri , or highly similar, such as for M. malmoense and M. szulgai , the 16S–23S rRNA gene ITS sequences were a helpful supplement for the differentiation of closely related species. As with the 16S rRNA gene sequence, M. marinum and M. ulcerans have identical ITS sequences, thus, cannot be differentiated utilizing this analysis [ 14 , 15 ].…”
Section: Species Identification Of Ntmmentioning
confidence: 99%